Groups whose orders factorise into at most four primes. (January 2022) - Dietrich, Heiko; Eick, Bettina; Pan, Xueyu
Abstract: The groups whose orders factorise into at most four primes have been described (up to isomorphism) in various papers. Given such an order n, this paper exhibits a new explicit and compact determination of the isomorphism types of the groups of order n together with effective algorithms to enumerate, construct, and identify these groups. The algorithms are implemented for the computer algebra system GAP.